Characteristics of Tropical‐Cyclone Turbulence and Intensity Predictability. Issue 8 (15th April 2022) - Kieu, Chanh; Rotunno, Richard
Abstract: This study examines the characteristics of tropical‐cyclone (T‐C) turbulence and its related predictability implications. Using the Fourier‐Bessel spectral decomposition for convection‐permitting simulations, it is shown that T‐C turbulence possesses different spectral properties in the azimuthal and radial directions, with a steeper power law in the radial‐wavenumber than that in the azimuthal‐wavenumber direction. This spectral difference between the azimuthal and radial directions prevents one from using a single wavenumber to interpret T‐C intensity predictability as for classical homogeneous isotropic turbulence. Analyses of spectral error growth for a high‐wavenumber perturbation further confirm that the spectral growth is more rapid for high azimuthal wavenumbers than for the radial wavenumbers, reaching saturation after ∼9 hr and ∼18 hr for the azimuthal and radial directions, respectively. This result highlights the key difficulty in quantifying T‐C intensity predictability based on spectral upscale error growth for future applications. Plain Language Summary: This study examines the characteristics of tropical cyclone (T‐C) turbulence and related predictability implications. We show that T‐C turbulence possesses different spectral properties in the azimuthal and radial directions. This spectral difference between the azimuthal and radial directions prevents one from using a single wavenumber to interpret T‐C intensity predictability as for classical homogeneous isotropic turbulence. Our analyses of spectral kinetic energy error growth at the quasi‐stationary stage reveal that the spectral growth is more rapid for azimuthal wavenumbers, reaching saturation after ∼9 hr as compared to ∼18 hr for the radial direction. This study highlights the difficulty in quantifying T‐C intensity predictability based on spectral upscale error growth for practical applications. Key Points: Tropical‐cyclone (T‐C) convective‐scale turbulence is not isotropic/homogeneous, thus possessing different predictability properties from classical turbulence T‐C error‐energy spectra show distinct characteristics with a steeper power law in the radial direction than that in the azimuthal direction T‐C error energy spectral growth is more rapid for the azimuthal wavenumbers than for radial wavenumbers, reaching saturation after ∼18 hr